2022
DOI: 10.1021/acs.est.1c07921
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impact of the Development in Household Waste Management in China

Abstract: The potential climate change impacts of the development in Chinese household waste management, with less landfilling, more incineration with energy recovery, and source-separated food waste treated in biorefineries, were assessed through a life cycle assessment. When the waste management system interacts with a fossil-based energy system, landfilling produces a load of 144 kg CO2-eq/ton wet waste, while incineration shows a saving of 36 kg CO2-eq/ton wet waste. The introduction of food waste source separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The calculated carbon footprint of Scenario B was about 68 kg CO 2 -eq/t-FW compared to Scenario A (BAU) with 214 kg CO 2 -eq/t-FW for source-separated FW. In a recent study, authors found the source-segregated FW can lower climate change impacts by 33 kg CO 2 -eq/t-FW at a 60% source efficiency. A decentralized AcD system (Scenario B) could decrease carbon emissions by ∼32,000 kg of CO 2 -eq per year (with a transportation distance of 10 km), and a decentralized AcD system inside the campus (see Pathway 1 (P1), assuming AcD without transportation) would further reduce carbon emissions by ∼631 kg of CO 2 -eq per year, compared to the composting system (BAU).…”
Section: Resultsmentioning
confidence: 99%
“…The calculated carbon footprint of Scenario B was about 68 kg CO 2 -eq/t-FW compared to Scenario A (BAU) with 214 kg CO 2 -eq/t-FW for source-separated FW. In a recent study, authors found the source-segregated FW can lower climate change impacts by 33 kg CO 2 -eq/t-FW at a 60% source efficiency. A decentralized AcD system (Scenario B) could decrease carbon emissions by ∼32,000 kg of CO 2 -eq per year (with a transportation distance of 10 km), and a decentralized AcD system inside the campus (see Pathway 1 (P1), assuming AcD without transportation) would further reduce carbon emissions by ∼631 kg of CO 2 -eq per year, compared to the composting system (BAU).…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, the assessment of direct carbon emissions stemming from waste incineration predominantly relied on the physical composition of the incinerated waste. , However, the physical composition of waste entails significant labor efforts, and most of the studies have a low frequency of physical composition investigation and often use data from previous years or from specific studies conducted within the same year, which may not accurately reflect the current situation. , It is worth noting that the physical composition of waste can vary substantially due to changes in waste management policies and seasonal fluctuations . Consequently, relying on outdated waste composition data can lead to delayed accounting results that do not effectively represent the current levels of direct carbon emissions from waste incineration facilities.…”
Section: Resultsmentioning
confidence: 99%
“…5 Meanwhile, the GWP of incineration will increase significantly if waste management interacts with a non-fossil-based energy system. 6 As to biological technologies including composting and AD, land application of compost and digestate is important for their high greenhouse reduction potential; 4,7 unfortunately, it is the most challenging in practice. The market acceptance of compost products derived from FW is limited due to the concern about the potential secondary pollutants during land use.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The high moisture content and low calorific value of FW are not conducive to the stable operation of incineration, and the chloride salt contained is one of the possible precursors of dioxins . Meanwhile, the GWP of incineration will increase significantly if waste management interacts with a non-fossil-based energy system . As to biological technologies including composting and AD, land application of compost and digestate is important for their high greenhouse reduction potential; , unfortunately, it is the most challenging in practice.…”
Section: Introductionmentioning
confidence: 99%